IN-VITRO STUDIES OF PREDNISOLONE PRE-FORMULATIONS RELEASED FROM VARIOUS OINTMENT-BASES, FACTORS AFFECTING PENETRATION RATE AND PENETRATED AMOUNT - A. A., Mohamed; Zessin, G. (Gezira Journal of Health Sciences, 2008)
In this pre-formulation study, the effect of individual factors influencing the penetration rate of drugs incorporated in various topical vehicles has been in-vitro investigated. The water poor soluble prednisolone is chosen as a model drug. To increase the dissolution behavior of prednisolone (P), co-precipitates of it with polyvinyl-pyrrolidone 25 , (P/PVP 25 -coprs), polyethylene glycol 6000 , (P/PEG 6000 -coprs) and adsorbents with Aerosil 200 (P/A- 200 -adsrob) were prepared and in-vitro tested. A significantly increased dissolution in purified water was obtained with the co-precipitate F 1 , consisting of 10-wt% prednisolone and 90-wt% PEG 6000 . As F 1 was incorporated in various model-vehicles insignificant penetration profile was achieved. This effect was in fact due to the high concentration of PEG 6000 in the vehicles, which has increased the bulk viscosity of the ointments, that resulted on the one hand in restricted drug particles movement between the phases and on the other between the external phase and the artificial membrane. In contrast, F 2 consisted of 50-wt% Prednisolone and 50-wt.%/ PEG 6000 -copr, showed a slight increase in drug solubility compared to the corresponding physical mixture as well to pure P. As F 2 was incorporated in aqueous emulsifying wool wax-base, (WHES) a greater penetration rate into the synthetic membranes has resulted, and no change in the crystal form of P could be observed throughout the study time period of 70 hours. All other pre-formulations, (prefs) showed negligible increase in the solubility of P. X-ray diffractions studies of prednisolone-PVP 25 -coprs and those of drug/Aerosil 200 -adsorbent, indicated changes in the crystal form of P into monohydrate, which probably happened during the co-precipitation and adsorption of the drug and also during the incorporation of the pre-formulations into ointments. This change was specifically due to the very few amount of water present in ethanol 96 %v/v used as solvent for the preparation of the P-co-precipitates and adsorbents (= prefs) and also due to water available in the external phase of all used o/w-emulsions type ointment-bases.